Basic Notion of Infrastructure Asset Management What UNIID should do? - Hitapriya Suprayitno; Ria Asih Aryani Soemitro (Institut Teknologi Sepuluh Nopember, 2017)
Infrastructure Asset Management is important. In the developed countries the IAM has been implemented largely and deeply; and its give significant positive result. In Indonesia, the IAM is not yet popular, it is just recently started. The IAM need to be implemented more and better in Indonesia. Three main questions concerning UNIID and the IAM : what the IAM is, how the IAM Practices are and what UNIID should do. The main program to be realized is a creation of IAM Group in UNIID. The main duty of this group is participating in developing more and better IAM Practice in Indonesia.